The past and coming communication journey in Malaysia - Idid, Syed Arabi (School of Media and Communication Studies (MENTION), Faculty of Sciences and Humanities, University Kebangsaan Malaysia, 2014)
The paper recorded the tremendous changes in the academic and media landscape in tracing the development of communication studies since its beginning in 1971. Universiti Sains Malaysia (USM) was the first to offer the communication programme followed by Universiti Technology MARA (UiTM), Universiti Kebangsaan Malaysia (UKM) and the other public universities. USM and UiTM benefitted from the American experts in the preparation of their academic programmes. The early communication programmes in public universities were American oriented due to the presence of the local lecturers whose early post graduate training was from American universities. This paper traced the turnover of academic staff in “generational order” to record such changes had on the development of the programme. The first generation of lecturers in the communication programmes has been taken over by the third and fourth generation compared to the new universities that only recorded the first generation of lecturers. The paper then discussed the challenges faced by the communication programmes in public universities such as the growth of the communication programmes in private universities, the lack of academic staff, and the adoption of the new media technology.